HUBUNGAN STRUKTUR ORGANISASI DAN STRES DENGAN KOMITMEN ORGANISASIONAL GURU SMA GONZAGA JAKARTA - Petrus Hari Prasetyo; Witarsa Tambunan (Jurnal Manajemen Pendidikan, 2014)
Professionalism of teachers requires a commitment in his work. This is the frame and the crown of life for a teacher. The challenge in many organizational commitment influenced by many factors, including organizational culture, organizational structure, leadership, leadership style, work environment, ability, personality, motivation of teachers, job satisfaction, teamwork, stress levels of teachers and other factors.This research is aimed for knowing the correlatiob between organization structure and stress on teacher organizational commitment. This research was conducted at SMA Gonzaga Jakarta by applying method of survey and correlation technique. The treatment research have been analysis by the test validity that using Pearson Product Moment correlation and the test realibity is calculated using the formula of Alpha Cronbach. The analytical requirement is normality test by Kolmogorov Smirnov, andd regression linearity test. While the hypothesis test uses simple correlation test, double correlation and regression linier and double regression. In this study, selected 35 teachers from the foundation as the unit of analysis because it hand an attachment to the organization.The result of data analysis indicates that: (1) There is positive and significant correlation between organization structure of organizational commitment with correlation coefficient 0,483 and determination coefficient 0,234 or 23,4%. (2) There is positive and significant correlation between stress of organizational commitment with correlation coefficient 0,589 and determination coefficient 0,347 or 34,7%.. (3) There is positive and significant correlation between organization structure and stress of organizational commitment with correlation coefficient 0,643 and determination coefficient 0,413 or 41,3%.Based on the results of the study can be stated as the following suggestions: (1) the teacher should be able to have self-control, able to establish communication, maintaining good physiological condition, fisikologis and maintain the behavior in order to enhance personal commitment, (2) the principal must have the ability to coordinate, empower and be a good partner for teachers, (3) the foundation must be a good home and can provide fair rights for teachers, (4) further research is needed to determine the commitment of teachers such as leadership, motivation, organizational culture and job satisfaction so that may obtainother information about efforts to increase the organizational commitment of teachers.Keywords : organization structure, stress, organizational commitment teacher